2017
DOI: 10.1007/s13201-017-0528-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of geochemical processes on hydrochemistry and irrigation suitability of groundwater in part of semi-arid Deccan Plateau, India

Abstract: Major ion geochemistry was used to characterise the chemical composition of groundwater in part of semiarid Deccan plateau region to understand the geochemical evolution and to evaluate the groundwater quality for irrigation. The study area comprises peninsular gneissic complex of Archean age, younger granites and basaltic alluvium. Forty-nine georeferenced groundwater samples were collected and analysed for major ions. The ionic sequence based on relative proportions was Na. High Na ? , Mg 2? and Ca 2? were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In the most recent studies, researchers found that rock-water interaction and evaporation are the main reasons for the water quality deterioration in this region (Das et al 2017;Narsimha and Sudarshan 2017;Venkateshwarlu and Reddy 2017). Findings from studies by Vasu et al (2017) and Adimalla and Venkatayogi (2018) also suggest the influence of rock-water interaction in addition to silicate weathering and reverse ion exchange towards the groundwater chemical evolution. In most instances, the groundwater was found to be unsuitable for household uses and marginal for irrigation purpose (Unnisa and Bi 2017).…”
Section: Introductionmentioning
confidence: 97%
“…In the most recent studies, researchers found that rock-water interaction and evaporation are the main reasons for the water quality deterioration in this region (Das et al 2017;Narsimha and Sudarshan 2017;Venkateshwarlu and Reddy 2017). Findings from studies by Vasu et al (2017) and Adimalla and Venkatayogi (2018) also suggest the influence of rock-water interaction in addition to silicate weathering and reverse ion exchange towards the groundwater chemical evolution. In most instances, the groundwater was found to be unsuitable for household uses and marginal for irrigation purpose (Unnisa and Bi 2017).…”
Section: Introductionmentioning
confidence: 97%
“…Na + , Ca 2+ , and Mg 2+ were found as the leading cations (pie and Schoeller diagrams, Figures 5 and 6, respectively) in our study area. The Ca 2+ /Mg 2+ ratio of 1 indicates dolomite liquefaction and >2 indicates silicate mineral weathering [129]. In the study area, 8.33% of the samples had Ca 2+ /Mg 2+ ratios less than 1 and 75% had ratios between 1 and 2, indicating dissolution of dolomite and calcite due to higher concentrations of Ca 2+ and Mg 2+ .…”
Section: Ion Dominancementioning
confidence: 87%
“…Ariful Alam, Md. Nazrul Islam, Ayesha Afrin, and Health Impact Analysis of Groundwater for Drinking Ferdausi Ali, Shahidul Islam and Sumon Ganguli in the University of Chittagong, Bangladesh minerals over bicarbonate [129]. Only 4 samples (16.67%) lay below the 1:1 equiline, indicating bicarbonate zone caused by the reaction of carbonic acid with feldspar.…”
Section: Ion Dominancementioning
confidence: 98%
See 1 more Smart Citation
“…2shows that almost all cold springs, Orok River and Orok warm spring are along the equiline, indicating that the abundance of these ions is mainly due to the weathering of carbonates (calcite and dolomite) (Mora et al, 2017). For Sebau hot spring (2012 and 2019) shows those points fall above the equiline, indicating that dolomite or montmorillonite secondary minerals dissolution was the primary process determining the chemical of groundwater (Vasu et al, 2017). While, Kalak and Rinjani hot springs show those points fall below the equiline, indicating gypsum or anhydrite dissolution was the primary process determining the chemical of groundwater.…”
Section: Hydrochemical Control Of Groundwatermentioning
confidence: 98%